Double alkyl chain copolymers as flow improvers for heavy oil. (3rd May 2017) - Liu, Jia-Wei; Mao, Jin-Cheng; Wang, Hai-Bin; Zhang, Zhao-Yang; Zhao, Jin-Zhou
ABSTRACT: As flow improvers for heavy crude oil, two oil-soluble copolymers (DM-S-VA, DA-S-VA) were successfully synthesized and characterized by 1 H NMR and GPC. A rich alkyl chain and appropriate molecular weight of copolymer play fundamental role in viscosity reduction of heavy oil. Furthermore, synergistic effect of surfactants on polymers can promote the viscosity reduction, and the best formulation can increase the viscosity reduction rate to 78% to oil A. Comparing with the apparent viscosity of the different heavy oil mixing system in a wide shear rate range (0.1–200 s −1 ), the results show good stability and viscosity reducing effect.